NEW INSIGHTS INTO CYTOMEGALOVIRUS INFECTION - Daminov F. A.; Karimova M. M.; Mustafоkulova Sh. R. (Web of Journals Publishing, 2025)
CMVI is an infection caused by a pathogen from the beta-herpesvirus group, characterised by diverse manifestations ranging from asymptomatic to generalised course with severe damage to the CNS and other organs. CMV infection is widespread [5,6,7].
Keywords: Cytomegalovirus infection, risk of infection, foetus, primary infection, secondary infection.